Plasma 1α-Hydroxycorticosterone as Biomarker for Acute Stress in Catsharks (Scyliorhinus canicula) - Ruiz-Jarabo, Ignacio; Barragán-Méndez, Cristina; Jerez-Cepa, Ismael; Fernández-Castro, Miriam; Sobrino, Ignacio; Mancera, Juan M.; Aerts, Johan (Frontiers in Physiology, 2019)
Glucocorticoids are pleiotropic steroid hormones mediating redistribution of energy. They induce breakdown of glycogen stores and consequent plasma hyperglycaemia after stressful situations. Glucocorticoid actions in most vertebrate species are exerted by cortisol and corticosterone. However, 1α-hydroxycorticosterone is the dominant corticosteroid hormone in elasmobranchs, though its effects as a glucocorticoid are unknown. Here we demonstrate, by using ultra-performance liquid chromatography coupled to tandem mass spectrometry for the quantification of 1α-hydroxycorticosterone in plasma of the elasmobranch Scyliorhinus canicula, the response of this hormone to an acute-stress situation and for the first time its glucocorticoid action in elasmobranchs. After an acute air-exposure challenge, S. canicula increased plasma levels of 1α-hydroxycorticosterone altogether with enhanced glycolysis and gluconeogenesis pathways to fuel energy demanding tissues, such as white muscle, during the first hours after the stress situation. We foresee our study as a starting point to evaluate stress responses in elasmobranchs, as well as for future applications in the management of these key ecosystem species.